Theorizing the local : music, practice, and experience in South Asia and beyond. - Wolf, Richard K. (Oxford University Press, 2009)
Over the past four decades, the "globalized" aspects of cultural circulation have received the majority of scholarly-and consumer-attention, particularly in the study of South Asian music. As a result, a broad range of community-based and other locally focused performance traditions in the regions of South Asia have remained relatively unexplored. Theorizing the Local provides a challenging and compelling counterperspective to the "globalized," arguing for the value of comparative microstudies that are not concerned primarily with the flow of capital and neoliberal politics. What does it mean for musical activities to be local in an increasingly interconnected world? To what extent can theoretical activity be localized to the very acts of making music, interacting, and composing? Theorizing the Local offers glimpses into rich musical worlds of south and west Asia, worlds which have never before been presented in a single volume. The authors cross the traditional borders of scholarship and region, exploring in unmatched detail a vast array of musical practices and significant ethnographic discoveries-from Nepal to India, India to Sri Lanka, Pakistan to Iran. Enriched by audio and video tracks on an extensive companion Web site, Theorizing the Local is an important study of South Asian musical traditions that offers a broader understanding of 21st-century music of the world -- Présentation de l'éditeur.